Comment: From the Armchair to the Toilet: McGinn's Evolutionary Tale of Disgust. (July 2014) - Clark, Jason A.
Strohminger (2014) criticizes McGinn for his lack of attention to recent scientific findings, and for ignoring common sense. This commentary deepens both of these criticisms via an exploration of McGinn's account of the evolution of disgust.